Assessment of the Fisheries Status in River Molo to Guide the Management on its Fisheries - Kobingi , Nyakeya; Kiptoo , Kipkorir K. G.; Nyamora , Jane; Kerich , Emmy Cheptoo (African Journal of Education,Science and Technology (AJEST), 2018)
Rivers provide a suite of ecosystem goods and services to fisheries as well as water that benefit the domestic and industrial use of the riparian communities. The increasing intensification of human activities along River Molo in the Rift Valley, Kenya continues to affect the diversity of aquatic life including fish. Whereas, information on the status and changes in fish population and ecological attributes along the river that is fundamental, knowledge is currently lacking. The study evaluated the status of River Molo fisheries for the purposes of guiding it management. Fish species abundance and distribution, food and feeding habits, length/weight relationships and maturity stages were the main fisheries structure parameters determined. There was a significant difference in the fish catch data based on the sampling location and fish species (P < 0.05). The minimum sizes at which the species mature was established to be 24 cm for Clarias theodorae, 25 cm for Oreochromis niloticus baringoensis, 17 cm for Barbus altenialis, 23 cm for Labeo cylindricus and 13.5 cm for Barbus cercops. There were differences in the sex ratios of the species with Barbus altenialis and Barbus neumayeri being the only species where males dominated over the female. Only Labeo cylindricus exhibited a positive allometric growth (b < 3). Although overfishing was not noted, an analysis of the breeding trends indicated recruitment overfishing took place sometimes in the past few years. These observations suggest that less favorable hydrological conditions coupled with coincidental high fishing pressure could have impacted the river’s population biomass. The need for River Molo fisheries management plan with a single economic vision of the resource use based on an ecosystem-oriented approach cannot be overstated. The plan should capture among other components, the hydrological regime, and species life history traits, fishing impacts and stakeholders socioeconomic requirements as key elements for fishery sustainability.